HOW DOES THE EFFECT OF CORPORATE ETHICS AND POLITICAL BAHAVIOR AGAINST ORGANIZATIONAL COMMITMENTS? - Robbie, Iqbal (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The ethical value is part of the organizational culture, as an organizational environment that plays a role in forming employee organizational commitment. This study aims to determine the effect of a ethical values on organizational commitment with political behavior as a mediating variable. This research is a positivist approach or a quantitative approach because it tests existing variables. The ethical value is based on the diversity of situations and conditions in the company and personal behavior within the leader in using political influence to enable conflict or good synergy between employees. The population of this study were all employees other than the Head of the Office both PNS and non PNS under the Investment and Integrated Services Office of the Pasuruan City Government, amounting to 90 people. Research variables will be elaborated through a questionnaire which will be distributed to respondents based on the total number, because it uses census research. The collected data will be processed using smart PLS analysist